Early silicification of the Cyrenaican chert, Libya: The importance of moganite as a transitional silicon dioxide phase. Issue 2 (6th December 2020) - El‐Hawat, Ahmed S.; El‐Ghali, Mohamed A.K.; McLaren, Sue J.; Kemp, Simon J.
Abstract: The Messinian lagoonal carbonate–evaporite sequence of Cyrenaica, north‐east Libya, hosts: (i) opaline nodules in gypsiferous microbial‐rich mudstone; (ii) nodules replacing poikilotopic gypsum cementing bioclastic carbonates; and (iii) bedded porcelanite with large lenticular gypsum pseudomorphs intercalated with recrystallized microbial mats. Optical microscopy, scanning electron microscopy, backscattered electron images – secondary electron images, X‐ray fluorescence, X‐ray diffraction and cathodoluminescence techniques were employed to elucidate on the early stages of chert diagenesis and demonstrate the role of moganite in the formation of varieties of chalcedony during silicification. The opaline nodules composed of opal‐A, exhibit shrinkage cracks lined by isopachous fibrous quartzine underlain by a thin birefringent zone. This suggests that quartzine may develop by crystallization and conversion of opal‐A through a transitional moganite. The quartzine is followed by amorphous silica gel that converts into length‐fast chalcedony. By contrast, lutecite evolved by silica replacement of gypsum through a transitional moganite phase, which forms an amorphous zone in apparent optical continuity with the fibrous lutecite; as moganite advances by pseudo‐crystalline terminations controlled by the gypsum cleavage. In gypsified oyster shells, intercrystalline organic matter enveloping pseudomorphed shell microstructures enabled moganite nucleation that merges syntaxially around the gypsum crystal rim. The associated lutecite occurs as radial‐fibrous beekite aggregates that are consistent with early shell silicification. The bedded porcelanite consists of opal‐CT groundmass undergoing recrystallization and enclosing micro‐cavities lined by quartzine. The associated pseudomorphs display phases of gypsum replacement by moganite and lutecite at the outer margin, followed by dissolution and cavity filling by quartz varieties in response to fluid flushing. In all cases, organic matter and microbes played a vital role in the silicification process.